2018
DOI: 10.1515/sjecr-2017-0032
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing of Biodegradable Scaffolds to Engineer Artificial Blood Vessel

Abstract: Blood vessels diseases such as cardiac infarction with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In another study reported by Milosevic et al (248) have prepared synthetic scaffold for the artificial blood vessel grafting in which outer layer of suture was prepared from electrospun PCL on the inner layer of porous PCL-PEG copolymer. The biomechanical properties, the pore size of these scaffolds was found to adequate for scaffold materials, however, the authors did not cultured cells to corroborate the potential of this material in vivo.…”
Section: Fibers Of Bps Obtained Via Electrospinningmentioning
confidence: 99%
“…In another study reported by Milosevic et al (248) have prepared synthetic scaffold for the artificial blood vessel grafting in which outer layer of suture was prepared from electrospun PCL on the inner layer of porous PCL-PEG copolymer. The biomechanical properties, the pore size of these scaffolds was found to adequate for scaffold materials, however, the authors did not cultured cells to corroborate the potential of this material in vivo.…”
Section: Fibers Of Bps Obtained Via Electrospinningmentioning
confidence: 99%